High thermal resistance polyimide separators prepared via soluble precusor and non-solvent induced phase separation process for lithium ion batteries. (1st January 2016) - Zhang, Hong; Lin, Chun-Er; Zhou, Ming-Yong; John, Angelin Ebanezar; Zhu, Bao-Ku
Highlights: For the first time, a sponge-like microporous PI separators were prepared via Soluble Precusor and Non-solvent Induced Phase Separation Process for Lithium Ion Batteries. This PI separator with high porosity and pore-connectivity was successfully prepared by the incorporation of PEX. This PI separator behaved high thermal stability and excellent electrochemical properties compared with the PP separator. Abstract: Lithium ion battery separators with excellent thermal stability are highly desired to meet the requirements of electric vehicles. Basing on the excellent natures of PMDA-ODA polymide (PI) and processibility of the corresponding precursor solution of polyamic acid (PAA), the porous PI separators were prepared from the PAA precursor via non-solvent induced phase separation (NIPS) and thermal imidization process. By controlling the NIPS process, the ideal PI separator with high porosity and pore-connectivity was successfully obtained and employed in lithium ion batteries (LIBs). Besides the quite high thermal stability, this PI separator behaved excellent wettability in the liquid electrolyte and high liquid electrolyte uptake. By activated with liquid electrolyte, the ionic conductivity of the PI separator could reach as high as 2.15 mS·cm −1 . Compared with the cells with the typical PP separators, the cells assembled with the PI separators performed the lower resistance, the higher discharge capacity and the better rate capability. These results suggested that the PAA-NIPS process could be an efficient and applicable route for preparing high performance PI separators.